Rozwój rolnictwa ekologicznego na Dolnym Śląsku - Golinowska, Maria; Janowska-Biernat, Justyna (Development of Ecological Agriculture in Lower Silesia, 2006)
When the Act of ecological agriculture took effect in 2001, and later amendments were introduced in 2004, it caused a dynamic development of this kind of agricultural production in Poland and Lower Silesia. In 2004 in Lower Silesia there were registered 197 farms which received financial support for that sort of activity. The farms put to market typically agricultural products, such as: cereals, potatoes, vegetables, orchard fruit (apples, strawberries, currants, chokeberries) and a range of animal products (eggs, hens, goats, goat milk, rabbits, different kinds of meat and honey).Within this market Lower Silesia has a remarkable share in the production of wheat (Triticum aestivum ssp.speltum), oats, rye, apples, honey, goats and laying hens. In 2005 the number of farms increased by 5 thousands and now it amounts to 9 thousands. This system of agricultural production is likely to keep developing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 244-250